Lagrangian dust model simulations for a case of moist convective dust emission and transport in the western Sahara region during Fennec/LADUNEX. Issue 12 (23rd June 2015) - Sodemann, H.; Lai, T. M.; Marenco, F.; Ryder, C. L.; Flamant, C.; Knippertz, P.; Rosenberg, P.; Bart, M.; McQuaid, J. B.
Abstract Due to the harshness and inaccessibility of desert regions, the uncertainties concerning the processes of dust mobilization at the surface, airborne transport, and sedimentation are still considerable, limiting the ability to perform model simulations. In June 2011, a comprehensive data set of ground‐based and airborne in situ measurements and remote sensing observations was acquired within the Fennec/Lagrangian Dust Source Inversion Experiment (LADUNEX) field campaign in the western Sahara region. Here we evaluate the ability of the state‐of‐the‐art Lagrangian particle dispersion model FLEXPART, newly fitted with a dust mobilization capability, to simulate dust transport in this region. We investigate a case where a large mesoscale convective system (MCS) triggered dust emissions in central Mali, which subsequently moved as a large cold pool dust front toward northern Mauritania. Specifying dust mobilization for this case is shown to be an important obstacle to simulating dust transport during this event, since neither the MCS nor the associated cold pool‐causing dust emission is represented in the meteorological analysis. Obtaining a realistic dust transport simulation for this case therefore requires an inversion approach using a manual specification of the dust sources supported by satellite imagery. When compared to in situ and remote sensing data from two aircraft, the Lagrangian dust transport simulations represent the overall shape and evolution of the dust plume well. While accumulation and coarse mode dust are well represented in the simulation, giant mode particles are considerably underestimated. Our results re‐emphasize that dust emission associated with deep moist convection remains a key issue for reliable dust model simulations in northern Africa.